Characterization of cryptic complex chromosome rearrangements in balanced chromosomal rearrangement carriers and their PGT-SR clinical outcome assessments - Dehua Cheng; Hebatallah Ibrahim; Keli Luo; Yifan Gu; Pingyuan Xie; Yanqin Xiao; Jingpeng Cai; Xianhong Wu; Ge Lin; Yueqiu Tan; Liang Hu (Scientific Reports, 2024)
Abstract Several reports have presented that balanced chromosomal rearrangements (BCRs) carriers with normal phenotypes may be carriers of complex rearrangements. However, the incidence and PGT clinical outcomes of cryptic complex chromosome rearrangements (CCCRs) in individuals with BCRs is remain unknown. We recruited a cohort of 1,264 individuals with BCR carriers from 2016 to 2021 at the Reproductive and Genetic Hospital of CITIC Xiangya. Peripheral blood was collected for karyotyping and genomic DNA extraction and the PGT-SR clinical outcomes of CCCRs carriers were analyzed and compared with those of BCR carriers. Our findings revealed that 3.6% (45/1,264) of BCR carriers had CCCRs, involving 3–25 breakpoints on 1–3 chromosomes. Furthermore, when mate-pair sequencing was employed, 63.3% (19/30) of CCCR carriers were found to have chromosome rearrangements that were different from those identified by the MicroSeq technique. And the transferable embryo rate of CCCR carriers with 3 chromosomes was significantly lower than that of CCCR carriers with only 1–2 chromosomes. In this research, we revealed that some of the BCR carriers were actually CCCR carriers, and the prognosis of PGT in CCCR carriers with one or two chromosomes is better than that of CCCR carriers with three chromosomes.